Traditional healing and antimicrobial role of the herbal drug against UTIs by ethnic people of Darjeeling tea gardens, India - D Chettri; S Pradhan
The herbal age-old traditional method is practiced even today to treat Urinary Tract Infection (UTI) by the ethnic inhabitants of tea gardens of Darjeeling Himalaya, India. The aim of this study was to explore and document the traditional ways of healing UTIs. The information was collected from selected tea gardens and data was quantitatively analyzed with the help of ethnobotanical indices viz., use value, plant part value, family use value, fidelity level (%), and informant consensus factor. Antibiogram of four UTI-causing bacteria (Escherichia coli, Pseudomonas aeruginosa, Proteus vulgaris and Staphylococcus aureus) was also established by Kirbye Bauer$1 (Bs disc diffusion method. Antibacterial activity of twelve mostly used plants like Cheliocostus speciosus, Equisetum diffusum, Saccharum officinarum, Elettaria cardamomum, Coriandrum sativum, Plantago asiatica ssp. erosa, Centella asiatica, Achyranthes bidentata, Carex cruciata, Drymaria cordata ssp. diandra, Nephrolepis cordifolia, Malvaviscus arboreus were assessed against the aforementioned bacterial strains. Drymaria cordata and Centella asiatica on comparative MIC and MBC study showed the lowest MIC and MBC value of 0.29 mg/mL each against Staphylococcus, representing their effectivity. Nephrolepis cordifolia with 100% FL showed the lowest MIC and MBC value 0.67 mg/mL each against E. coli K12. The uses of these plants known from the ethnomedicinal knowledge of the healers could be promoted as complementary medicine to treat UTI. s